Analysis of the effect of swimmer's head position on swimming performance using computational fluid dynamics - Zaidi, H.; Taiar, R.; Fohanno, S.; Polidori, G. (Journal of Biomechanics, 2008)
The aim of this numerical work is to analyze the effect of the position of the swimmer's head on the hydrodynamic performances in swimming. In this initial study, the problem was modeled as 2D and in steady hydrodynamic state. The geometry is generated by the CAD software CATIA© and the numerical simulation is carried out by the use of the CFD Fluent code. The standard k-e turbulence model is used with a specific wall law. Three positions of the head were studied, for a range of Reynolds numbers about 106. The obtained numerical results revealed that the position of the head had a noticeable effect on the hydrodynamic performances, strongly modifying the wake around the swimmer. The analysis of these results made it possible to propose an optimal position of the head of a swimmer in underwater swimming.